PENGARUH MODEL PEMBELAJARAN DISCOVERY TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA TERPADU KELAS VIII DI SMPN 1 SUELA TAHUN PELAJARAN 2018/2019 - Muhammad Rizal; Nunung Ariandani (Cocos Bio, 2023)
Research conducted at SMPN 1 Suela aims to determine the effect of Discovery learning models on student learning outcomes in Biology subjects in class VIII SMPN 1 Suela Kec. Suela The research design used was quasi-experiment using pre-test and post-test of control class and experimental class. The study population was 171 students, while the sample for the control class was 25 students and the experiment was 25 students. Data about learning outcomes in Biology subjects is collected by multiple choice tests. Data analysis using t-test statistics. The results showed that there was a significant influence using Discovery learning models. Discovery learning model of the experimental class at the time of pre-test average value of 65.28 and post-test average value of 79.04 while the control class that uses conventional learning models at the time of pre-test average value of 65.12 and the average value of post test average of 72. And based on calculations using the t-test obtained t count (6.76) is greater than t table with a significant level of 5%. with degrees of freedom (dk) n_1 + n_2-2 = 25 + 25 = 48, obtained t table of 2.0126. This shows that t_ (count˃) t_table is 6.76 ˃ 2.0126. From these results it shows that Ha is accepted, meaning that there is a significant influence by using the Discovery learning model on student learning outcomes in Biology subject class VIII at SMPN 1 Suela Academic Year 2019.